Aortoenteric Fistula Assocaited with Acute Myocardial Infarcation - Robert J Fingerote; Alan BR Thomson (Canadian Journal of Gastroenterology)
A 64-year-old male with a prior abdominal aortic graft for lower limb ischemia presented with melena and myocardial infarction. Despite aggressive investigation, an aortoenteric fistula was not diagnosed until after massive gastrointestinal hemorrhage. The patient's myocardial infarction may have heen precipitated by hypotension induced by hemorrhage through the aortoenteric fistula. Patients with prior abdominal aortic graft surgery presenting with gastrointestinal bleeding, abdominal pain or occult sepsis need to be aggressively investigated to determine whether an aortoenteric fistula is present. Laparotomy should be done in such patients if no cause for these symptoms can be determined.